Improved Cardiac Function and Attenuated Inflammatory Response by Additional Administration of Tirofiban during PCI for ST-Segment Elevation Myocardial Infarction Patients. (16th June 2021) - Zhang, Jing; Ding, Guomin
Abstract : ST-segment elevation myocardial infarction (STEMI) is one of the acute coronary syndromes, and it is the main cause of cardiac death worldwide. The purpose of this study was to investigate whether tirofiban improves cardiac function and attenuates inflammatory response in STEMI patients undergoing percutaneous coronary intervention (PCI). From May 2016 to May 2019, a total of 124 patients who admitted into our hospital due to STEMI fulfilled inclusion and exclusion criteria and were randomly assigned to PCI + tirofiban and PCI groups, 62 cases per groups. Intravenous administration of 10  μ g kg −1 min −1 tirofiban was performed 30 min prior to PCI. During PCI, tirofiban infusion through a micropump with 0.15  μ g kg −1 min −1 lasted for 48 h. It was found that the PCI + tirofiban group was significantly different from the PCI group in total corrected TIMI frame count (CTFC) after PCI (15.88 ± 5.11 vs. 22.47 ± 6.26, P < 0.001 ). At day 7 and day 30 post-PCI, a significant time-dependent decrease in the levels of brain natriuretic peptide (BNP), cardiac troponin I (cTnI), and creatine kinase isoenzyme (CK-MB) in both groups was observed after PCI (P < 0.001 ). More importantly, the patients in the PCI + tirofiban group had much lower levels of BNP, cTnI, and CK-MB compared with those in the PCI group at days 7 and 30 post-PCI (P < 0.001 ). At day 7 following PCI, the left ventricular ejection fraction (LVEF) was statistically higher in the PCI + tirofiban group than in the PCI group (P < 0.05 ). At day 30 post-PCI, increased LVEF concomitant with reduced left ventricular end diastolic diameter (LVEDD) and left ventricular end systolic diameter (LVESD) was observed in the PCI + tirofiban group compared with the PCI group. At day 7 and day 30 post-PCI, both groups displayed a time-dependent decline in the levels of C reactive protein (CRP), tumor necrosis factor- α (TNF- α ), interleukin-6 (IL-6), and procalcitonin (PCT) after PCI (P < 0.05 ). Additionally, the patients in the PCI + tirofiban group had lower levels of CRP, TNF- α, IL-6, and PCT compared with those in the PCI group at days 7 and 30 post-PCI (P < 0.05 ). All patients in the PCI + tirofiban and PCI groups were followed up for 12 months by outpatient or telephone after discharge. There were fewer patients with LVEF < 50% in the PCI + tirofiban group than the PCI group (P = 0.044 ). Furthermore, it was found that the incidence rate of major adverse cardiovascular events (MACEs) in the PCI + tirofiban group was evidently lower than that in the PCI group (12.90% vs. 29.03%, P = 0.028 ). Taken together, our data suggest that additional administration of tirofiban could improve cardiac function and attenuate inflammatory response in STEMI patients undergoing PCI, which is worthy of promotion in clinic.